Vloga slovenščine kot prvega jezika pri poučevanju nemščine kot drugega/tretjega jezika - Leskovec, Mojca (Jezik in slovstvo, 2018)
In the history of foreign language didactics, the role of the first language in teaching further languages has been overlooked for a long time. In modern foreign language classrooms, however, it has found its place again, as such classrooms follow didactic-methodological principles, including plurilingualism. The main goal of foreign language teaching is the development of communicative competence, which, according to the Common European Framework of Reference for Languages, is formed through the interrelation and interaction of all of the languages one has learned. Slovenian syllabi for German foresee the integration of the first language. The aim of a survey conducted among Slovenian teachers of German was to determine how often they integrate Slovenian as a first language of the majority into German-as-a-second/third-language classrooms and for what purpose. Most of the teachers defined the frequency as low. Two-thirds of the participants include Slovenian for comparative analysis, while more than half of them use Slovenian when explaining grammar. The most common reason for not including Slovenian in German-as-a-second/third-language classrooms more often was the belief that foreign language classes should be taught in the target language.
Keywords: didaktično-metodična načela; nemščina kot drugi/tretji jezik; poučevanje nemščine; raznojezičnost; SEJO; slovenščina; slovenščina kot prvi jezik; učni načrti